도시부 도로 제한속도 상향에 따른 교통영향 분석 연구 - 최정택 (The Graduate School, Ajou University, 2024)
2021년 4월 17일 전국적으로 동시 시행한 「안전속도 5030」정책은 교통사고 발생을 줄여 사망자 감소와 보행자 안전을 담보하기 위한 효과 적인 정책이긴 하나 교통운영의 효율적인 측면에서 부족함이 있다는 지적이 있어 왔다. 특히, 일률적으로 도시부 일반도로의 제한속도를 50km/h로 하향하고, 또한 어린이보호구역 또는 이면도로에서 제한속도를 30km/h로 하향함에 따라 운전자들의 불만과 교통 효율성 저하의 문제가 지적되었다. 이러한 이유로 최근 여러 지자체에서 도시부 일반도로 제한속도를 50km/h에서 60km/h로 상향을 추진하고 있으나 이에 대한 객관적인 교통량 및 속도와 관련된 교통 흐름 개선 효과 등에 대한 연구 없이 경험에 의한 제한속도 상향을 추진하고 있다. 본 연구에서는 스마트 교차로 구축 사업이 종료된 지자체의 도시부 일반도로의 제한속도가 현재 50km/h인 구간의 교통량 및 신호운영 자료를 수집하여 교통 시뮬레이션 툴인 Synchro와 VISSIM을 이용하여 다양한 시나리오 기반으로 분석함에 따라 도시부 일반도로 제한속도 상향에 대한 객관적인 효과 및 시사점 도출과 더불어 제한속도 상향 이전과 이후에 대하여 문헌 자료에 의한 교통사고 조사 분석을 병행 하였다. 더불어 본 연구를 통해 얻어진 도시부 일반도로 제한속도에 따른 교통량 및 속도와의 관계를 통해 제한속도 상향에 대한 객관적인 근거를 제시하고 이를 기반으로 일률적인 제한속도 설정이 아닌 차로수와 도로 주변 환경을 고려한 제한속도 설정방안을 제시하였다.|The "Safety Speed 5030" policy, which was implemented nationwide on April 17, 2021, is an effective policy to reduce traffic accidents to reduce deaths and ensure pedestrian safety, but it has been pointed out that it lacks in terms of efficiency in traffic operation. In particular, drivers' complaints and problems with reduced traffic efficiency were pointed out as the speed limit on general roads in the city was lowered to 50km/h and the speed limit was lowered to 30km/h in children's protection zones or back roads._x000D_ For this reason, various local governments have recently been pushing for an increase in the speed limit of the city's general road from 50km/h to 60km/h, but they are pushing for an increase in the speed limit based on experience without research on the effect of improving traffic flow related to objective traffic volume and speed._x000D_ In this study, traffic volume and signal operation data for the section where the speed limit on the urban general road of the local government is currently 50 km/h, and traffic simulation tools Synchro and VISSIM were used to analyze them based on various scenarios._x000D_ In addition, an objective basis for increasing the speed limit was presented through the relationship between traffic volume and speed according to the city's general road speed obtained through this study, and based on this, a speed limit setting plan was proposed that considers the number of lanes and the surrounding environment of the road, not a uniform speed setting.
학위논문(석사)--교통ITS학과,2024. 2
Keywords: 교통영향; 도시부 도로; 제한속도 상향